Load Balancing Routing Algorithm Based on Genetic Optimization and Artificial Bee Colony in LEO Satellite Network - Xia DENG; Miaomiao HAO; Wucheng LIN (天地一体化信息网络)
The LEO satellite network become a powerful complement to the terrestrial network as it shows the advantage of low latency, low cost, low loss rate and global coverage.However, due to the uneven distribution of users and the variation of network traffic over time, some links may be congested and unbalanced.A load balancing routing algorithm based on genetic optimization and artificial bee colony in LEO satellite networks(GABC) was proposed, which combined genetic algorithm with artificial bee colony algorithm to avoid local optimization.Experimental results showed that compared with the shortest path routing and LBRA-CP algorithm, the proposed algorithm has higher data transmission rate and throughput with lower delay and overhead ratio.